2012
DOI: 10.1038/ja.2011.123
|View full text |Cite
|
Sign up to set email alerts
|

Virgaricin produced by Virgaria sp. FKI-4860

Abstract: The genus Virgaria was first proposed in 1817 1 and classified in the family Xylariaceae. 2 Virgaria nigra, a type species of Virgaria, is a commonly encountered hyphomycetes and has been illustrated in numerous publications. [3][4][5] However, little work has been done on the chemical constituents of Virgaria species, and only one compound, vinigrol, has previously been isolated from V. nigra. 6 As part of our interest in the presence of novel metabolites in Virgaria sp., we investigated the chemical constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Chemical constituents of the fungus Virgaria have also previously been studied by Ando et al, 1 but only two compounds had been isolated so far, of which one is identified in our previous study. 2 In the present study, chemical reinvestigation of V. boninensis FKI-4958 has resulted in the isolation of three additional new natural products, cinatrins D (1) and E (2), and virgaricin B (3). V. boninensis FKI-4860 strain produced 4 (but not 1, 2 and 3).…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…Chemical constituents of the fungus Virgaria have also previously been studied by Ando et al, 1 but only two compounds had been isolated so far, of which one is identified in our previous study. 2 In the present study, chemical reinvestigation of V. boninensis FKI-4958 has resulted in the isolation of three additional new natural products, cinatrins D (1) and E (2), and virgaricin B (3). V. boninensis FKI-4860 strain produced 4 (but not 1, 2 and 3).…”
Section: Resultsmentioning
confidence: 80%
“…The structures of these known compounds were confirmed by comparison of their spectroscopic data with those reported in the literature. 2,[6][7][8] Details of the fermentation and isolation of the known compounds from the culture broth of FKI-6621 strain are described in the Supplementary Information.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19 We discovered more than 30 novel compounds (including unpublished) from screening using 1500 fungal strains from 2005 to 2010. [20][21][22] The producers of the novel compounds were classified as species level, and 63% of them were new (or potential) species. 10,17,23 In this study, Trichoderma sp.…”
Section: Discussionmentioning
confidence: 99%